Soot formation in asymmetrical ethylene jet flame-wall interactions. (February 2023) - Luo, Minye; Ren, Hang; Chen, Chen; Liu, Dong
Abstract: Soot from asymmetrical flame-wall interactions in inclined ethylene jet diffusion impinging flames was studied. The soot morphology, nanostructure and oxidation reactivity were acquired via transmission electron spectroscopy, high resolution transmission electron spectroscopy and thermogravimetric analyzer. Effects of oblique burner angles (θ), Reynolds numbers (Re) and nozzle to plate distances (H) on soot formation and evolution were analyzed. The results showed soot from downhill position presented the higher crystallization degree and the lower oxidation reactivity than soot from uphill position due to the asymmetrical FWI. With θ increased, the promoting effect of the plate on combustion was enhanced at the downhill side and was impaired at the uphill side. The oxidation reactivity of soot with lower crystallization degree from uphill position was improved, while the opposite variation trend was observed from downhill position. Soot from both uphill and downhill positions has the higher carbonization degree and the lower reactivity when Re increased. Soot particles had the shorter fringe length and larger fringe tortuosity and presented the higher reactivity with the augment of H. The reduction of the velocity perpendicular to the wall with the extension of free jet region suppressed soot formation and evolution at uphill and downhill sides. Highlights: Asymmetrical flame-wall interactions significantly affect soot characteristics. Soot from the downhill position has the lower oxidation reactivity. Augment of θ improves the oxidation reactivity of soot from uphill positions. Increase of Re enhances uphill and downhill position soot carbonization degree. Increase of H promotes uphill and downhill position soot oxidation reactivity.